"Nordic' hamstrings exercise - Engagement characteristics and training responses - Iga, J.; Fruer, C. S.; Deighan, M.; Croix, M.D. S.; James, D.V. B. (International Journal of Sports Medicine, 2012)
The present study examined the neuromuscular activation characteristics of the hamstrings during the `Nordic' hamstrings exercise (NHE) and changes in the eccentric strength of the knee flexors with NHE training. Initially, the normalised root mean square electromyographic (EMG) activity of the hamstrings of both limbs during various phases (90-61°, 60-31° and 30-0° of knee extension) of the NHE were determined in 18 soccer players. Subsequently participants were randomly allocated to either a training (n=10) or control group. The isokinetic eccentric peak torques of the dominant and non-dominant limbs were recorded at 60, 120 and 240°/s pre- and post-training. The EMG values of both limbs were comparable (P=0.184) and greater EMG activity was recorded at more extended knee positions of the NHE (P=0.001). 4 weeks of NHE training significantly improved peak torque by up to 21% in all assessment conditions. Data indicate the hamstrings of both limbs are engaged identically during the NHE and training results in gains in the eccentric peak torque of the hamstrings of both limbs; these gains may augment the force that the hamstrings can withstand when forcefully stretched, attenuating injury risk.